Effect of insecticide-treated bed nets on visceral leishmaniasis incidence in Bangladesh. A retrospective cohort analysis. - Rajib Chowdhury; Vashkar Chowdhury; Shyla Faria; Sakila Akter; Aditya Prasad Dash; Sujit Kumar Bhattacharya; Narayan Prosad Maheswary; Caryn Bern; Shireen Akhter; Jorge Alvar; Axel Kroeger; Marleen Boelaert; et al. (PLOS Neglected Tropical Diseases, 2019)
BACKGROUND:Visceral leishmaniasis (VL) is a parasitic disease, transmitted by the sand fly species Phlebotomus argentipes in the Indian sub-continent. Effective vector control is highly desirable to reduce vector density and human and vector contact in the endemic communities with the aim to curtail disease transmission. We evaluated the effect of long lasting insecticide treated bed nets (LLIN) and bed nets impregnated with slow-release insecticide tablet K-O TAB 1-2-3 (jointly insecticide-treated nets or ITN) on VL incidence in a highly endemic sub-district (upazila) in Bangladesh. METHODS:Several distributions of LLIN or K-O TAB 1-2-3 for self-impregnation of bed nets at home took place in Fulbaria upazila, Mymensigh district from 2004 to 2008 under three research projects, respectively funded by CDC, Atlanta, USA (2004) and WHO-TDR, Geneva, Switzerland (2006 & 2008). We included all households (n = 8142) in the 20 villages that had benefited in the past from one of these interventions (1295 donated LLIN and 11,918 local bed nets impregnated with K-O TAB 1-2-3) in the "exposed cohort". We recruited a "non-exposed cohort" in villages with contemporaneously similar incidence rates who had not received such vector control interventions (7729 HHs from nine villages). In both cohorts, we visited all families house to house and ascertained any VL cases for the 3 year period before and after the intervention. We evaluated the incidence rate (IR) of VL in both cohorts as primary endpoint, applying the difference-in-differences method. RESULTS:The study identified 1011 VL cases (IR 140.47/10,000 per year [py]) before the intervention, of which 534 and 477 cases in the intervention and control areas respectively. The IR was 144.13/10,000 py (534/37050) and 136.59/10,000 py (477/34923) in the intervention and control areas respectively, with no significant difference (p = 0.3901) before the intervention. After the intervention, a total of 555 cases (IR 77.11/10,000 py) were identified of which 178 (IR 48.04/10,000 ...